Demographic factors and innovative work behaviour of Malaysian school teachers - Masrek, Mohamad Noorman; Baharuddin, Mohammad Fazli; Mohamed Shuhidan, Shamila (Faculty of Information Management, 2025)
The emergence of Industrial Revolution 4.0 (IR 4.0) has changed several factors that drive worker capabilities and skills in a more inventive direction. Digital transformation necessitates digital literacy and technical expertise, as well as continual microlearning and personal development across employee engagement and commitment. However, studies found that, employees still seen not competent and innovative, which include teachers. Therefore, the objective of the study is to examine the perceived level of innovative work behaviour among Malaysian school teachers. In addition, it also explores the demographic factors against the innovative work behaviour. Adopting the survey research method, the study collected data using self-administered questionnaire. Drawing upon 356 usable responses the data were analysed statistically using descriptive and inferential statistic. The results showed that Malaysian teachers, generally perceived that their level of innovative work behaviour to be high. Except for length of service, no significant difference could be observed in terms of innovative work behaviour across other demographic factors, namely age, gender, grade level and education level. The findings suggest that innovation among Malaysian school teachers are very overwhelming and demographic factors have mixed bearing in shaping this form of behaviour.